Respuesta :
Answer:
The Answer is: a^2 + 2ab + b^2
Step-by-step explanation:
Multiply the first factor resulting in the a squared, then the two inner factors resulting in ab + ab, finally the last term, resulting in b squared. Then combine terms:
(-a - b)(-a - b) =
a^2 + ab + ab + b^2 =
a^2 + 2ab + b^2
Hope this helps! Have an awesome day! :-)
Answer: a^2 + b^2+2ab
Step-by-step explanation: (-a-b)(-a-b) = a^2 + ab + ab + b^2 =
a^2 + b^2 + 2ab
![Ver imagen jojo880](https://us-static.z-dn.net/files/d29/72b2fd03416b594ef0173d6a518f95f2.jpg)